Developing “Digital Intuition” in Primary School Students: A New Generation of Digital Safety Pedagogy - qizi, Kurbanova Muslima Khakimjon (Journal of Innovation in Education and Social Research, 2025)
This article analyzes the theoretical and practical foundations of developing digital intuition in the process of primary education, defined as students’ ability to make quick, independent, and logical decisions in a digital environment. Digital literacy, algorithmic thinking, and competencies for solving problem situations through digital tools are highlighted as leading directions of modern primary education. The article proposes effective methods for expanding students’ independent thinking, creative approaches, and rapid decision-making abilities through the use of innovative educational technologies, multimedia tasks, digital games, and artificial intelligence. The study also presents the pedagogical advantages of developing digital intuition, practical examples, and methodological recommendations that can serve as a guide for teachers.